A systematic review and comparative evaluation to develop and validate a comprehensive framework for cancer surveillance systems - Mohsen Soleimani; Marjan GhaziSaeedi; Seyed Mohammad Ayyoubzadeh; Ahmad Jalilvand (Archives of Public Health)
Abstract Background The increasing global burden of cancer necessitates robust cancer surveillance systems to generate accurate and comprehensive data for effective public health interventions. Despite advancements, significant gaps remain in data standardization, interoperability, and adaptability to diverse healthcare settings. This study aims to develop and validate a comprehensive framework for cancer surveillance systems that addresses these gaps, ensuring enhanced global applicability and regional relevance. Methods A systematic review was conducted following PRISMA guidelines, analyzing 13 studies selected from an initial pool of 1,085 articles retrieved from five major databases: PubMed, Embase, Scopus, Web of Science, and IEEE. Additionally, a comparative evaluation of 13 international cancer surveillance systems was performed to identify critical data elements and practices. Key indicators were extracted. A researcher-designed checklist consolidating these elements was validated through expert consultation with a response rate of 82% (n = 14), achieving high reliability (Cronbach’s alpha = 0.849). Results The proposed framework addresses critical gaps in existing cancer surveillance systems by integrating a comprehensive set of epidemiological indicators, including incidence, prevalence, mortality, survival rates, years lived with disability, and years of life lost, calculated using multiple standard populations for age-standardized rates. Furthermore, the framework incorporates key demographic filters such as age, sex, and geographic location to enable stratified analyses. It also includes advanced data elements, such as cancer type classification based on ICD-O standards, ensuring precision, consistency, and enhanced comparability across diverse cancer datasets. Conclusion The validated framework provides a structured and adaptable approach to cancer data collection and analysis, enhancing public health decision-making and resource allocation. By addressing current limitations, this study offers a significant advancement in cancer surveillance methodologies, with potential applications in diverse healthcare contexts globally. Clinical trial registration Clinical trial number: Not applicable